Comparing the uplink performance of 3D and 2D antenna models in THz networks in the presence of joint human and wall blockages - Tahniyat Aslam; Irfan Ahmed; Sundus Ali (PLoS ONE, 2026)
Terahertz (THz) communication is considered as a key technology enabler for realizing Sixth Generation (6G) network. THz band communication offers several promising advantages, but numerous challenges are expected due to the inherent limitations of propagation at THz frequencies in the 6G network, such as path loss, interference, human and wall blockages, etc. In retrospect, THz band communication finds its use in indoor network deployments. In this paper, a framework is developed to analyze the impact of the uplink performance of a single-tier THz network, incorporating the impact of wall and human blockages in the indoor environment. To model a practical system, 3D antenna model have been employed, which accounts for both horizontal and vertical radiation patterns, whose performance have been benchmarked against 2D antenna model that accounts only for horizontal direction. This evaluation has enabled us to highlight the impact of practical antenna models on THz communication performance. Using the developed system model, generalized expressions for uplink mean interference, uplink coverage probability, and area spectral efficiency have been derived. The impact of THz uplink network performance has been analyzed using an antenna model with varying user equipment heights and different main lobe beam widths, as well as considering different path loss exponents for Line-of-Sight (LOS) and Non-Line-of-Sight (NLOS) conditions. The analytical results obtained against different network conditions have been compared and validated against Monte Carlo simulations and both have been found in agreement.